PENGARUH PEMBERIAN BERBAGAI TAKARAN SERASAH TANAMAN UBI KAYU TERHADAP PERTUMBUHAN BIBIT METE DAN KETAHANANNYA TERHADAP SERANGAN HAMA WERENG PUCUK METE (Sanurus indecora) DI PEMBIBITAN - Nurmas, Andi; Mallarangeng, Rahayu; Mursalim, Soleha (Jurnal Agroteknos, 2012)
This research was conducted at the New Campus Anduonohu, Kendari from December 2011 to March 2012. The purpose of this study was to determine the effect of various doses of  cassava plant litter  on  the  growth of  cashew seedlings and  resistance to  pest  attack planthopper shoots cashew in the nurseries. The design of the study was Randomized Block Design (RBD) with 4 levels of treatment that were: treatment without cassava plant litter +(U0), the provision of cassava plant litter 40 g polybag-1, equivalent to 10 ton ha-1 (U1), the provision of cassava plant litter 80 g polybag-1, equivalent to 20 ton ha-1 (U2), the provision of cassava plant litter 120 g of polybag-1, equivalent to 30 ton ha-1 (U3) and each treatment was repeated 3 times so that there were 12 experimental units and each treatment used 2 cashew seedlings,therefore overall cashew seedlings used was 24 cashew seedlings. The results showed that administration of various doses of the cassava plant litter showed no significant effect on plant height, leaf number, stem diameter ages 60  and 90 days after planting, leaf area, dashed ratio of plant roots and dry weight and had significant effect on stem diameter age 30 days after planting. The intensity of hopper pests of cashew shoots (Sanurus indecora) obtained the highest treatment without cassava plant litter with the intensity of attacks and the lowest 13,9% obtained in the treatment of 10 ton ha-1, 20 ton ha-1 and 30 ton ha-1 with 2,8% intensity of attacks. Keywords: cassava plant litter, cashew seedlings, and Sanurus indecora.